Sustainable leadership practices among schools principals and their relationship with teacher commitment in Malaysia rural school - Muhammad Hasrizal Abdul Rahim,; Mohd Izham Mohd Hamzah,; Aida Hanim A. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Through sustainable leadership practices school are able to maintain their missions and goals in facing difficulties and challenges. Such a practice enhances teacher commitment, especially in shaping a better school working environment in achieving the organization goals. Past studies have found a significant link between sustainable leadership practices and the teacher commitment. However, there has been little discussion about the phenomenal relationship in rural National Secondary School context. Hence, this study surveyed the level of sustainable leadership practices among school principals and the teacher commitment in SMK in rural part of Malaysia. It also investigated whether there is a relationship between both variables. Using proportionate random sampling, 450 teachers represented the sample. Due of the COVID-19 epidemic and the research population's remote location, data were collected via mail. The findings revealed that principals had a high level of sustainable leadership practises (M = 4.18, SD = 0.52) as well as a very high degree of teacher commitment (M = 4.33, SD = 0.45). Teacher commitment was also positively connected with sustainable leadership practises (r = 0.503, p 0.05). The Ministry of Education Malaysia can apply these findings to improve sustainable leadership practises in the National Education Principals Professional Qualifications, which are intended exclusively for future Malaysian school principals. In this perspective, it is hoped that these findings will contribute to the body of knowledge on sustainable leadership practises and teacher commitment.